A Systematic Literature Review on Dividend Policy: Theories, Determinants, and Firm Outcomes - Sulistyowati, Tussi; Anwar, Khairil; Pardosi, Pardomuan (Asosiasi Ide Bahasa Kepri, 2025)
This study conducted a qualitative systematic literature review (SLR) to critically evaluate recent research on dividend policy, focusing on publications from 2021 to 2025. Using the PRISMA guidelines, the review identified and organized literature into three key categories: theoretical foundations, determinants of dividend decisions, and the outcomes of dividend policy on firm performance. The study highlighted the use of major theories such as Agency Theory, the Cost of Equity Hypothesis, and Signaling Theory, which continue to shape the understanding of dividend behavior. It also examined various internal factors—such as profitability, liquidity, and corporate governance—and external influences, including macroeconomic conditions and Environmental, Social, and Governance (ESG) performance, as significant determinants of dividend decisions. The review found that dividend policies have a notable impact on firm profitability, market valuation, and investor perception, especially in periods of uncertainty. Additionally, the study recognized a growing interest in how ESG considerations influence payout strategies. Future research directions include exploring the integration of ESG metrics into dividend models, examining the role of economic cycles and financial crises (e.g., COVID-19), and assessing the implications of technological advancements and digital finance on dividend strategies and broader corporate governance frameworks.